Creating opportunities for Cardiology training in South Africa - Pecoraro, AJK; Herbst, PG (SA Heart Journal, 2025)
South Africa continues to see a rise in the prevalence of cardiovascular disease, as is the case for many low- to middle-income countries. This growing cardiovascular disease burden, combined with rapidly evolving treatment modalities, requiring the acquisition of novel skills by practitioners, places an ever-increasing strain on the country’s limited number of cardiologists.